2007
DOI: 10.1002/pbc.20829
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus 7 in pediatric hematopoietic stem cell transplantation

Abstract: HHV-7 was uncommon post-HSCT. It was associated with severe GVHD and sepsis secondary to severe immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In studies on both adult and pediatric patients HHV-7 viremia post-transplant is ranging from 10% to 57% [Hubacek et al, 2008]. Nevertheless, in another study on pediatric stem cell recipients, the incidence of HHV-7 was found to be 5.5% [Khanani et al, 2007].…”
Section: Human Herpesvirus-6/human Herpesvirus-7 Basic Characteristicsmentioning
confidence: 95%
See 2 more Smart Citations
“…In studies on both adult and pediatric patients HHV-7 viremia post-transplant is ranging from 10% to 57% [Hubacek et al, 2008]. Nevertheless, in another study on pediatric stem cell recipients, the incidence of HHV-7 was found to be 5.5% [Khanani et al, 2007].…”
Section: Human Herpesvirus-6/human Herpesvirus-7 Basic Characteristicsmentioning
confidence: 95%
“…HHV-6A, HHV-6B, and HHV-7 are ubiquitous and remain latent in T cells after the primary infection and then can be reactivated in an immunocompromised host [Khanani et al, 2007]. The phenomenon of HHV-6 chromosomal integration (CI), a latent state of the virus in the chromosome, should be kept in mind as an alternative cause of HHV-6 detection in suspected cases [Ljungman et al, 2008].…”
Section: Human Herpesvirus-6/human Herpesvirus-7 Basic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include CNS disease [53], myelosuppression [54], aGVHD [55], and allograft dysfunction and rejection [56]. Data from a number of studies suggest a potential indirect effect of HHV-7 to increase rates of CMV reactivation and disease in HCT [57] and SOT [58,59] recipients, but this is not a consistent finding [52].…”
Section: Human Herpesvirusmentioning
confidence: 99%
“…16,19 Moreover, HHV-7 was associated with severe GvHD and sepsis secondary to severe immunosuppression after HSCT from matched unrelated donors. 20 HHV-8 has been associated with the development of visceral Kaposi's sarcoma or lymphomas in immunocompromised patients, [21][22][23] and de Medeiros et al 24 have reported a case of Kaposi's sarcoma after allogeneic HSCT. However, a survey on the presence of serum HHV-8 DNA after bone marrow transplantation performed in 187 Italian HSCT donor-recipient pairs did not show any HHV-8-related complications after a median of 6 years of follow-up.…”
Section: Allogeneic Hsctmentioning
confidence: 99%